2016
DOI: 10.1111/raq.12142
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis approach to the effects of live prey on the growth of Octopus vulgaris paralarvae under culture conditions

Abstract: The common octopus (Octopus vulgaris, Cuvier 1797) is a promising species for aquaculture diversification, but the massive mortality during the first life stage is the main bottleneck for its commercial production. The aim of the present study was to compare the effects of different live preys (Artemia and crustacean zoeae) and/or Artemia enrichment protocols in the paralarval growth by using a meta‐analysis approach. A total of 26 independent assays were used, including data from the bibliography and from exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 48 publications
5
47
1
Order By: Relevance
“…It has been suggested that the high mortality of paralarvae in captivity is due to a lack of knowledge regarding the physiology and nutrition of paralarvae (Domingues et al, 2003; Villanueva et al, 2009; Garrido et al, 2016a) or the lack of a suitable diet meeting all micronutrient requirements (Iglesias et al, 2007). Several experiments have shown that feeding new born paralarvae with different diet can influence its survival (Villanueva, 1994; Iglesias et al, 2004; Farías et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the high mortality of paralarvae in captivity is due to a lack of knowledge regarding the physiology and nutrition of paralarvae (Domingues et al, 2003; Villanueva et al, 2009; Garrido et al, 2016a) or the lack of a suitable diet meeting all micronutrient requirements (Iglesias et al, 2007). Several experiments have shown that feeding new born paralarvae with different diet can influence its survival (Villanueva, 1994; Iglesias et al, 2004; Farías et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, major efforts have been conducted to understand the nutritional needs for paralarvae in captivity (Garrido et al, 2016b) and their fatty acid profile in the wild (Estefanell et al, 2013; Garrido et al, 2016a), however the nutritional link between them and their prey in natural conditions is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…trituberculatus zoea is an attractive prey for common octopus paralarvae, which is in accordance with the fact that they feed on decapod crustacean larvae in the natural habitat (Olmos‐Pérez, Roura, Pierce, Boyer, & González, ; Roura, González, Redd, & Guerra, ). Although there have been a number of reports documenting the effectiveness of supplying crab zoeae as feed for paralarvae (Garrido et al, ; Iglesias et al, ; Roo et al, ; Villanueva, ), P . trituberculatus appeared to have great potential as paralarval prey in the mass production of juvenile octopus because of their high fecundity (attaining over a million zoeae per female) and the availability of ovigerous females from fishery landings (Hamasaki et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…vulgaris ’ (Iglesias et al, ; Okumura, Kurihara, Iwamoto, & Takeuchi, ); they share a characteristic meroplankton stage (a paralarva) early in their life cycle (Villanueva, Nozais, & Boletzky, ). They have great potential for aquaculture because of their rapid growth and high commercial value (Garrido et al, ; Iglesias et al, ; Vaz‐Pires, Seixas, & Barbosa, ). However, despite efforts spanning 50 years, reliable culture technology for paralarvae has not yet been established due to the severe mortality, poor growth and impairments of paralarvae that might be attributed mainly to inappropriate prey type and nutritional deficiency (Garrido et al, ; Iglesias et al, ; Itami, Izawa, Maeda, & Nakai, ; Vaz‐Pires et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation